The effect of electronic word of mouth (eWOM), prices, and cash on delivery (COD) services on consumer purchasing decisions on e-commerce applications - Melly Pefi Lara; Gesit Thabrani (Universitas Negeri Padang, 2022)
This take a look at pursuits to investigate the impact of electronic word of mouth (eWOM), prices, and coins on delivery (COD) offerings on client shopping choices on e-commerce programs in Pesisir Selatan. The populace used on this take a look at is humans who've e-commerce programs and the pattern used is humans who've e-trade programs in Pesisir Selatan as a minimum have one e-commerce application, even though now no longer but for on-line shopping, simply searching around. The wide variety of samples used on this take a look at have been one hundred seventy respondents. Data series is accomplished thru a web questionnaire (google form) and facts control the usage of the SPSS application. The consequences of this take a look at suggest that. (1) Electronic word of mouth (eWOM) has a fine and massive impact on client shopping choices on e-trade programs in Pesisir Selatan. (2) Price has a fine and massive impact on client shopping choices on e-commerce programs in Pesisir Selatan. (3) Cash on delivery (COD) offerings don't have any massive or no impact on client shopping choices on e- trade programs in Pesisir Selatan. The consequences of this take a look at suggest that buying choices are undoubtedly and extensively stimulated with the aid of using electronic word of mouth (eWOM) and prices, however aren't stimulated with the aid of using coins on delivery (COD) offerings.